Whither the liberal European Union energy model? The public policy consequences of Russia's weaponization of Energy - Andreas Goldthau; Nick Sitter (EconPol Forum, 2022)
Energy is primarily a private good but also has public goods characteristics. The EU's traditional strategy to cater to the strategic goods element - energy security - was the liberal market model. The Ukraine crisis has fundamentally put the liberal model in question. The present EU measures are deeply interventionist. Renewables are elevated to matters of national interest. Combined with massive public funds, this accelerates the clean transition and is likely to put structural breaks into the incumbent energy system. Going forward, the EU has three options: a return to the status quo ante (the liberal model); a more robust "public interest" model accounting for the risk of high political costs; and a Colbertist model putting the state in charge of managing markets and the clean transition . The Ukraine crisis highlights each model's political and economic trade-offs. Policy priorities and strategies need to be revisited in light of these trade-offs. This is a watershed moment in European energy policy
Keywords: 330